2001
DOI: 10.1016/s0014-5793(01)02262-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous subunit exchange in porcine liver fructose‐1,6‐bisphosphatase

Abstract: No evidence to date suggests the possibility of subunit exchange between tetramers of mammalian fructose-1,6-bisphosphatase. An engineered fructose-1,6-bisphosphatase, with subunits of altered electrostatic charge, exhibits spontaneous subunit exchange with wild-type enzyme in the absence of ligands. The exchange process reaches equilibrium in approximately 5 h at 4³C, as monitored by non-denaturing gel electrophoresis and anion exchange chromatography. Active site ligands, such as fructose 6-phosphate, abolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…The Hill coefficients for both Fru-1,6-P 2 and Mg 2ϩ are 1.1 Ϯ 0.1. These values are similar to those reported previously for E. coli FBPase (4, 14, 16), and differ from the porcine enzyme principally in the Hill coefficient for Mg 2ϩ , which for porcine FBPase is 1.9 Ϯ 0.1 (45).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The Hill coefficients for both Fru-1,6-P 2 and Mg 2ϩ are 1.1 Ϯ 0.1. These values are similar to those reported previously for E. coli FBPase (4, 14, 16), and differ from the porcine enzyme principally in the Hill coefficient for Mg 2ϩ , which for porcine FBPase is 1.9 Ϯ 0.1 (45).…”
Section: Resultssupporting
confidence: 90%
“…Porcine FBPase undergoes spontaneous subunit exchange (45,52,53). In the presence of Fru-1,6-P 2 or Fru-2,6-P 2 , exchange reactions involve only dimers of the tetramer (45,53).…”
Section: Discussionmentioning
confidence: 99%
“…2. In the presence of F16P 2 , subunit exchange occurs only at the level of C1/C2 dimers (28). Hence, protocol B leads to hybrids 4:0, 0:4, and 2:2p.…”
Section: Methodsmentioning
confidence: 99%
“…Anion-exchange chromatography cleanly separates most of the hybrid constructs (28). More recently, Kantrowitz and colleagues (29) reported that AMP must bind to two subunits of FBPase to cause significant inhibition.…”
mentioning
confidence: 99%
“…Since the human muscle and liver FBPase isoforms share only 76.9% sequence identity (89.3% homology) over 337 residues and the muscle isoform has additional functions in the cell, including higher sensitivity of hmFBPase to AMP and its regulation by Ca 2+ (Gizak et al, 2012;Pirog et al, 2014), some differences in their R/T transition behaviour might be expected. In solution, porcine FBPase subunits have been shown to exchange on a time scale of a few hours (Nelson et al, 2001), indicating flexibility at the interfaces. Thus, the possibly that the rotation angle of FBPases might sometimes be influenced by crystal-packing effects cannot be discounted entirely.…”
Section: Figurementioning
confidence: 99%